2011
DOI: 10.1021/ct200430c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lipid Diffusion and Mixing in Accelerated Molecular Dynamics

Abstract: Accelerated molecular dynamics (aMD) is an enhanced sampling technique that expedites conformational space sampling by reducing the barriers separating various low-energy states of a system. Here, we present the first application of the aMD method on lipid membranes. Altogether, ∼1.5 μs simulations were performed on three systems: a pure POPC bilayer, a pure DMPC bilayer, and a mixed POPC:DMPC bilayer. Overall, the aMD simulations are found to produce significant speedup in trans–gauche isomerization and lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 57 publications
2
59
0
Order By: Relevance
“…Wang et al examined acceleration of lateral diffusion and mixing of two lipid components by using the aMD method [85]. In their method, the dihedral potential was boosted, which enhances trans-gauche isomerization of lipid acyl chains during the simulation.…”
Section: Recent Membrane and Membrane Protein Simulations Using Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al examined acceleration of lateral diffusion and mixing of two lipid components by using the aMD method [85]. In their method, the dihedral potential was boosted, which enhances trans-gauche isomerization of lipid acyl chains during the simulation.…”
Section: Recent Membrane and Membrane Protein Simulations Using Enmentioning
confidence: 99%
“…To illustrate the accuracy and efficiency of different molecular models and enhanced sampling algorithms, we review recent simulations of glycophorin A (GpA) [72-75], phospholamban (PLN) [76-80], amyloid precursor protein (APP) [81-84], and mixed lipid bilayers [85-87]. In the simulations of GpA, PLN, and APP, REMD and REUS using implicit membrane models were mostly used to determine their conformational ensembles in membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The same group also presented the first application of the accelerated molecular dynamics (aMD) method to lipid membranes. It was found that the aMD simulations produce 2-3 fold speedups in lipid lateral diffusion versus those in conventional AAMD simulations 153,154 . However, neither the above AAMD simulations have produced a complete phase separation from a randomly mixed lipid (and cholesterol) mixtures.…”
Section: Computational Studies Of Cross-layer Couplingmentioning
confidence: 99%
“…For example, aMD simulations provide significant speed-up of the peptide conformational transitions[56, 99, 100], lipid diffusion and mixing[101], conformational transitions in proteins[89, 102105], protein folding[106, 107] and protein-ligand binding[108]. Notably, hundreds-of-nanosecond aMD simulations are to capture millisecond-timescale events in both globular and membrane proteins[109112].…”
Section: Unconstrained Enhanced Sampling Methodsmentioning
confidence: 99%